Aqra city at ottoman era with written books of Mosul historian Yasin bin khairyallah Alomari - Al-Jawadi, Ghassan W. (Humanities Journal of University of Zakho, 2015)
Aqra is considered one of the most important Bahdinan princedom cities in the ottoman era but It does not take the attention to be studied and researched academically . this city was given a certain care by Mosul historian in the ottoman era yasin bin khairyallah alomari who referred to its contribution in the princedom events its trade importance of a number of scholar so this research is written to show the role of this city at the time depending upon the written books of Alomari in which very significant information was mentioned about Aqra the research aims at urging the researchers to expand in studying its history by benefiting from 0ther resources from which the ottoman archives enriched to get a broader picture and fill out the gaps and more universal related to the history of this olden city .